Smart Readiness for buildings – ﻿Digital asset for energy transition - Maria Azzalin (Agathón)
The priority objective of the European Green Deal is the development of a fully integrated, interconnected and digitised energy market based on the use of renewable sources and the achievement of energy efficiency of buildings. Digital assets, digitalisation of processes and the adoption of smart and emerging technologies support the achievement of these conditions. In this scenario, the contribution introduces a critical overview of the principles and methodological aspects that have taught the definition of the Smart Readiness Indicator (SRI) within the energy transition process. The position paper opens to insights into the relationship between SRI objectives and the potential offered by digital assets and approaches based on the digital twin.